HIGH SCHOOL STUDENTS’ ABSENTEEISM IN ENGLISH CLASSES - Bekteshi, Edita (Social work and education, 2020)
This study deals with absenteeism in classes. Considering that the educational system pays little attention to this negative phenomenon, the existing challenges of absenteeism are more debatable issues than taking real action to eliminate them. This study, conducted among international students, aims to find out factors that affect absenteeism in English classes among public high school students. It further addresses the role of the teachers, the institutions and societies’ attitudes towards English and offers practical implications for all stakeholders of the educational system. It serves as a system to guide the institutions, the teachers and the students to overcome this educative obstacle and minimize its negative effect.